Getting Married in the Digital Age: An Exploration of Online Marriage Applications in Islamic Family Law - Harahap, Haddad Ulum; Harahap, Rijal 'Allamah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study aims to understand the practice of online marriage that can be integrated with the provisions stipulated in Islamic Family Law. In the growing digital age, the trend of online marriage is growing among the Muslim community. This has driven the need to adapt traditional wedding practices to digital technology. This research identifies and explores challenges in the integration between Islamic marriage practices and digital technologies. This research uses qualitative methodology with data collection through literature study and document analysis. The main results show that the integration of online marriage applications in Islamic Family Law is possible through specific adjustments to the provisions applicable to Islamic family law and the technology used, including digital identity verification and video conferencing for brides-to-be. As for prospective husbands, guardians, and witnesses are required to meet face to face offline in one assembly. The research also found that negotiating and recording dowries digitally can be done with transparency and in accordance with Islamic law. These results have significant implications for the practice of marriage in Islam, and show that with the right approach, technology can be a tool that enriches the practice of Islamic marriage, as well as enabling society to maintain traditions in this digital age. As such, the research contributes to an understanding of the adaptation of Islamic law in the digital age, and provides new insights into the potential and challenges of technological integration in Islamic marriage practice.